Winemaking by-products as a source of phenolic compounds: Comparative study of dehydration processes. (1st August 2022) - Souza da Costa, Bianca; Soldevilla Muro, Germán; Oliván García, Marta; Motilva, Maria-Jose
Abstract: The circular bioeconomy for the production of high-value products has gained attention due to new policies for the reuse and sustainable valorisation of locally available underutilised raw material in several countries. This study is focused to explore the potential of the by-products of winemaking through direct dehydration processes. The phenolic composition (anthocyanins and uncolored phenols) and their quantitative pattern in the skin, seeds and stems were determined by ultra-high performance liquid chromatography with tandem mass spectrometry (UHPLC-QqQ-MS/MS). The results showed that lyophilisation and mainly the Spiral Flash dryer, as the most feasible system for industrial application, could be a promising process for producing high added-value ingredients with retention of bioactive phenolic compounds. The skin fraction is a rich source of anthocyanins. In a complementary way, the seeds are an important source of hydroxybenzoic acids, procyanidins and lignans, a family of phenolic compounds little studied in grapes and wine. Regardless of the dehydration method, the stems are an important source of a wide range of phenolic compounds, mainly proanthocyanidins. The present study established that the winemaking process provides an excellent source of raw materials for the recovery of ingredients rich in valuable phenolic compounds, thus contributing to the circular bioeconomy. Graphical abstract: Image 1 Highlights: Circular bioeconomy for production of high-value ingredients rich in phenolics. Valorisation of locally-available underutilised winemaking by-products. Dehydration process to obtain products with a high shelf-stability. Targeted metabolomics to determine phenolic composition of winemaking by-products.